Enhanced UV Resistance and Improved Killing of Malaria Mosquitoes by Photolyase Transgenic Entomopathogenic Fungi - Fang, Weiguo; St. Leger, Raymond J. (PLOS ONE, 2012)
The low survival of microbial pest control agents exposed to UV is the major environmental factor limiting their effectiveness. Using gene disruption we demonstrated that the insect pathogenic fungus Metarhizium robertsii uses photolyases to remove UV-induced cyclobutane pyrimidine dimers (CPD) and pyrimidine (6-4) photoproducts [(6-4)PPs] from its DNA. However, this photorepair is insufficient to fix CPD lesions and prevent the loss of viability caused by seven hours of solar radiation. Expression of a highly efficient archaeal (Halobacterium salinarum) CPD photolyase increased photorepair >30-fold in both M. robertsii and Beauveria bassiana. Consequently, transgenic strains were much more resistant to sunlight and retained virulence against the malaria vector Anopheles gambiae. In the field this will translate into much more efficient pest control over a longer time period. Conversely, our data shows that deleting native photolyase genes will strictly contain M. robertsii to areas protected from sunlight, alleviating safety concerns that transgenic hypervirulent Metarhizium spp will spread from mosquito traps or houses. The precision and malleability of the native and transgenic photolyases allows design of multiple pathogens with different strategies based on the environments in which they will be used.